SEDIMENTARY MANGANESE METALLOGENESIS IN RESPONSE TO THE EVOLUTION OF THE EARTH SYSTEM - Roy S. (My University, 2006)
The concentration of manganese in solution and its precipitation in inorganic systems are primarily redox-controlled, guided by several Earth processes most of which were tectonically induced. The Early Archean atmosphere-hydrosphere system was extremely O2-deficient. Thus, the very high mantle heat flux producing superplumes, severe outgassing and high-temperature hydrothermal activity introduced substantial Mn2+ in anoxic oceans but prevented its precipitation. During the Late Archean, centered at ca. 2.75 Ga, the introduction of Photosystem II and decrease of the oxygen sinks led to a limited buildup of surface O2-content locally, initiating modest deposition of manganese in shallow basin-margin oxygenated niches (e.g., deposits in India and Brazil). Rapid burial of organic matter, decline of reduced gases from a progressively oxygenated mantle and a net increase in photosynthetic oxygen marked the Archean-Proterozoic transition. Concurrently, a massive drawdown of atmospheric CO2 owing to increased weathering rates on the tectonically expanded freeboard of the assembled supercontinents caused Paleoproterozoic glaciations (2.45-2.22 Ga). The spectacular sedimentary manganese deposits (at ca. 2.4 Ga) of Transvaal Supergroup, South Africa, were formed by oxidation of hydrothermally derived Mn2+ transferred from a stratified ocean to the continental shelf by transgression. Episodes of increased burial rate of organic matter during ca. 2.4 and 2.06 Ga are correlatable to ocean stratification and further rise of oxygen in the atmosphere. Black shale-hosted Mn carbonate deposits in the Birimian sequence (ca. 2.3-2.0 Ga), West Africa, its equivalents in South America and those in the Francevillian sequence (ca. 2.2-2.1 Ga), Gabon are correlatable to this period. Tectonically forced doming-up, attenuation and substantial increase in freeboard areas prompted increased silicate weathering and atmospheric CO2 drawdown causing glaciation on the Neoproterozoic Rodinia supercontinent. Tectonic rifting and mantle outgassing led to deglaciation. Dissolved Mn2+ and Fe2+ concentrated earlier in highly saline stagnant seawater below the ice cover were exported to shallow shelves by transgression during deglaciation. During the Sturtian glacial-interglacial event (ca. 750-700 Ma), interstratified Mn oxide and BIF deposits of Damara sequence, Namibia, was formed. The Varangian (≡ Marinoan; ca. 600 Ma) cryogenic event produced Mn oxide and BIF deposits at Urucum, Jacadigo Group, Brazil. The Datangpo interglacial sequence, South China (Liantuo-Nantuo ≡ Varangian event) contains black shale-hosted Mn carbonate deposits. The Early Paleozoic witnessed several glacioeustatic sea level changes producing small Mn carbonate deposits of Tiantaishan (Early Cambrian) and Taojiang (Mid-Ordovician) in black shale sequences, China, and the major Mn oxide-carbonate deposits of Karadzhal-type, Central Kazakhstan (Late Devonian). The Mesozoic period of intense plate movements and volcanism produced greenhouse climate and stratified oceans. During the Early Jurassic OAE, organic-rich sediments host many Mn carbonate deposits in Europe (e.g., Úrkút, Hungary) in black shale sequences. The Late Jurassic giant Mn Carbonate deposit at Molango, Mexico, was also genetically related to sea level change. Mn carbonates were always derived from Mn oxyhydroxides during early diagenesis. Large Mn oxide deposits of Cretaceous age at Groote Eylandt, Australia and Imini-Tasdremt, Morocco, were also formed during transgression-regression in greenhouse climate. The Early Oligocene giant Mn oxide-carbonate deposit of Chiatura (Georgia) and Nikopol (Ukraine) were developed in a similar situation. Thereafter, manganese sedimentation was entirely shifted to the deep seafloor and since ca. 15 Ma B.P. was climatically controlled (glaciation-deglaciation) assisted by oxygenated polar bottom currents (AABW, NADW). The changes in climate and the sea level were mainly tectonically forced. © 2006 Elsevier B.V. All rights reserved.
Keywords: MANGANESE; METALLOGENESIS; PALEOENVIRONMENT; SEDIMENTARY; Archean; Cretaceous; Jurassic; Devonian; Ordovician; Cambrian; Neoproterozoic; Paleoproterozoic; Oligocene; Precambrian::Archean; Докембрий::Архей; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Ordovician; Палеозой::Ордовикская; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен